Parameters design of a membrane-type restrictor with single-pad hydrostatic bearing to achieve high static stiffness. (March 2017) - Lai, Ta-Hua; Chang, Ting-Yu; Yang, Ya-Lu; Lin, Shih-Chieh
Abstract: The analysis described in this article shows that a high static stiffness of the bearing is attainable as two design parameters of membrane-type restrictor are properly chosen. The first one is the dimensionless stiffness of the membrane and the other one is the design restriction ratio of the bearing system. When the deformation-load relationship of the restrictor is compliance with the ideal trend, the stiffness of the bearing should theoretically approach infinite in most application range. It was derived that a dimensionless membrane stiffness of 1.33 and a design restriction ratio of 0.25 is the solution for such condition. The film thickness for the bearing will be maintained at designed levels over a loading range. Highlights: High static stiffness of bearing is attainable as two design parameters of membrane-type restrictor are properly chosen. The dimensionless stiffness of membrane is the key parameter that will affect the sign of the bearing stiffness. The design restriction ratio of the bearing system is another important design parameter and 0.25 is the optimal value. The optimal dimensionless stiffness of membrane is always 1.33 even different design restriction ratio was chosen. If the dimensionless stiffness of membrane is less than 1.33, negative stiffness will appear in certain loading range.